The causal impacts of empty stadiums on women`s sports activities: Evidence from European football leagues - Szabó, D. Z.; Kerényi, P. (Psychology of Sport and Exercise, 2023)
This paper examines the effect of spectators on women`s football games. COVID-19 and related restrictions provide a unique opportunity with an adequate sample size to test the effect of lockdown on sports activities. Studies have recently exploited this opportunity for men`s football to better understand the potential causes of home advantage and, more specifically, assess the psychological consequences when matches are played without supporters. Despite the increased scientific interest, there was only one paper that focused on women`s football. Therefore, we aim to contribute to this research field by considering matches from four major European women`s football leagues. The findings suggest that for three of these leagues, lockdown has a statistically significant effect on the sanctioned yellow cards by either reducing the number of yellow cards sanctioned to the away teams or increasing the number of yellow cards sanctioned to the home teams. Nonetheless, lockdown does not affect any final match outcomes; therefore, it does not significantly affect the magnitude of home advantage for women`s games.